Modern drifts in bioengineered nanoparticles toward insect pest management: a review - Pal, Sundar; Kumar, Abhishek; Baskar, David; Singh, Ashutosh; Kumar, Pradeep; Patel, Amit; Parmar, Arvind; Sarsiya, Vishal (Phytoprotection, 2021)
The development of molecular tools for agricultural analysis promoted property crop production improvement to rising food security from stress caused by organic phenomenon factors, as well as the insect pest attack. Crop productivity has inflated quintuple over the past few decades due to high-yielding varieties, irrigation, fertilizers, and pesticides. However, the planet population is anticipated to grow staggeringly over subsequent four decades, from nine to ten billion individuals. It’s so imperative to extend the assembly of food grains to feed the population. As way as ancient agriculture technology is bothered, it still incorporates a good distance to travel. The molecular tools wont to shield crops from organic phenomenon stress during this instance like plant alpha-amylase inhibitors, vacuolar ATPase, hemoprotein P450 monooxygenase, enzyme modulating oostatic issue (TMOF), enzyme inhibitors (PIs), with the exception of sterol enzyme (CHOx), lipoxygenases (enzyme), and technology, etc. despite not being wholesome. Additionally to delivery ecologically property farming practices into our daily lives, bionanotechnology will give opportunities for developing nations and developed nations shortly. It should have an enormous impact on farming systems while not the employment of pesticides. There area unit considerations concerning the food safety risks related to transgenic plants since the unfold of antibiotic resistance, the changes within the nutrient composition of plants, and also the production of noxious proteins and allergens can not be answered currently. Besides victimization high-yielding varieties, irrigation, and fertilizers, it’s a potent role in minimizing the economic losses caused by insects. Within the current context of insect pest management, it’s imperative to develop bionanotechnology-based tools for pest management. However, their economical use necessity takes for reckoning the numerous ecological role useful insect play for the longer-term development of agriculture.